2010
DOI: 10.1111/j.1365-2982.2009.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged IL-1β exposure alters neurotransmitter and electrically induced Ca2+responses in the myenteric plexus

Abstract: BACKGROUND Infection and inflammatory diseases of the gut results in profound changes of intestinal motor function. Acute administration of the pro-inflammatory cytokine interleukin-1beta (IL-1beta) was shown to have excitatory and neuromodulatory roles in the myenteric plexus. Here we aimed to study the effect of prolonged IL-1beta incubation on the response of myenteric neurones to different stimuli. METHODS Longitudinal muscle myenteric plexus preparations (LMMP's) of the guinea pig jejunum were incubated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
1
19
0
2
Order By: Relevance
“…Cytokine-induced modulation of enteric neurons can subsequently alter GI motility, absorption, secretion, and blood flow. Moreover, mucosal ion transport and epithelial permeability, in addition to enhancement of cholinergically mediated neurotransmission, are altered by proinflammatory cytokines such as IL-6 and IL-1␤ (24,30). Further support for IL-6 as a secretory cytokine is provided in its ability to suppress the inhibitory and antisecretory effects of norepinephrine by blocking its release from sympathetic fibers (37).…”
mentioning
confidence: 97%
“…Cytokine-induced modulation of enteric neurons can subsequently alter GI motility, absorption, secretion, and blood flow. Moreover, mucosal ion transport and epithelial permeability, in addition to enhancement of cholinergically mediated neurotransmission, are altered by proinflammatory cytokines such as IL-6 and IL-1␤ (24,30). Further support for IL-6 as a secretory cytokine is provided in its ability to suppress the inhibitory and antisecretory effects of norepinephrine by blocking its release from sympathetic fibers (37).…”
mentioning
confidence: 97%
“…Inflammatory mediators released by the infiltration may induce the alteration of GI motility. [18] An elevation of inflammatory factors, including IL-1β, TNF-α, and IL-6, was found in both IBD and postoperative ileus patients and it should be noted that in IBS patients, no pathomorphologic changes were observed, whereas the elevation of IL-6 was found in the region with gastrointestinal dyskinesis. [19] A study on gastroesophageal reflux disease showed that when the esophageal epithelial cells come in contact with the gastric juice, a great deal of IL-1β and IL-6 could be produced to reduce esophageal muscle contractility.…”
Section: Immunoinflammation and Fgidsmentioning
confidence: 99%
“…[18] As the concentration of IL-1β in smooth muscle ( in vitro ) perfusion groove was elevated from 10 -9 mol/L to 10 -8 mol/L, the open rate of Ca 2+ was increased from 17.3% to 24.7%; the result has indicated that IL-1β may directly act on Ca 2+ channel on GI smooth muscle cell membrane, thus affecting on the intestinal motility function.…”
Section: Mechanism Of Mediators Of Inflammation On the Progression Ofmentioning
confidence: 99%
“…Меха-нізм такого впливу багатогранний. Прозапальні цитокіни безпосередньо впливають на парієтальні клітини і пригнічують секрецію HCl, стимулюють синтез і виділення гастрину [27], пригнічують мото-рику травного тракту [17,23]. Що стосується секре-ції гастрину, на наш погляд, важливою є робота, в якій показано, що ІЛ-1β і ФНП-α можуть прямо ре-гулювати експресію гену гастрину через мітоген-активовану протеїнкіназу-і протеїнкіназа С-залеж-ний механізм [27].…”
unclassified
“…Kindt та співат. [23] показали, що однора-зове введення IЛ-1β відіграє збуджуючу і нейромо-дулюючу роль в міентеральному плетиві, проте тривала інкубація IЛ-1β з препаратом міентераль-ного плетива гладеньких м'язів порожньої кишки мурчаків дозо-залежно впливає на нейрональну відповідь і зростання концентрації іонізованого На сьогодні доведено, що IЛ-1β є сильним інгі-бітором скорочень гладеньких м'язових волокон тонкої кишки, клубової і товстої кишок у відповідь на ацетилхолін [4]. В цій роботі показано, що попе-реднє введення блокатора синтезу білка циклогек-симіду блокувало викликане IЛ-1β гальмування скорочень тонкої кишки, стимульованих ацетилхо-ліном, що дало авторам підстави припустити залу-чення нового синтезованого білку в цей ефект.…”
unclassified